Their Dreams and Ours: Britten, Film, and 'The Turn of the Screw' - Auker, Peter Leslie Roy (2021)
Britten’s 1954 opera The Turn of the Screw, based on Henry James’s ghost story, has been described by critics and academics as ‘cinematic’, but little serious academic study has been done to test this. Along with Peter Grimes, The Turn of the Screw is one of the most frequently filmed of Britten’s operas, mostly for television, some using location footage and/or studio work, and others based on live theatrical settings. This thesis explores the notion of cinematic opera in the context of The Turn of the Screw and filmed opera in general, and questions what inherent cinematic qualities exist in the work which make it particularly conducive for screen interpretation. The thesis will examine Britten’s engagement with film as both a cinemagoer and film music composer, and will find that these experiences informed his compositional and dramatic choices when creating The Turn of the Screw. Archival research reveals clues to the composer’s adaptation process by using a specific scene from the opera and unpicking its progress from the source story to stage production, via the development of Myfanwy Piper’s libretto and Britten’s score. A key part of the thesis looks at the subsequent interpretation of the opera on screen, using a case-study approach based on neoformalism as an analysis method, and referring to nearly a hundred screen shots. The case studies evaluate seven directors’ interpretations ranging from 1959 up to the 2010s, and include a study of Peter Morley’s 1959 ITV version which had previously been thought lost and was only rediscovered many years later. In addition, the influence of cinema on non-filmed productions of the opera will be assessed, together with an examination of the significance of non-opera screen adaptations of James’s story. Finally, in conclusion, the importance of other Britten operas on TV during his lifetime, and consideration of his TV opera Owen Wingrave as culmination of his engagement with film and TV will be examined.